If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (-1a + -5b + 6) * 3ab = 0 Reorder the terms: (6 + -1a + -5b) * 3ab = 0 Reorder the terms for easier multiplication: 3ab(6 + -1a + -5b) = 0 (6 * 3ab + -1a * 3ab + -5b * 3ab) = 0 Reorder the terms: (18ab + -15ab2 + -3a2b) = 0 (18ab + -15ab2 + -3a2b) = 0 Solving 18ab + -15ab2 + -3a2b = 0 Solving for variable 'a'. Factor out the Greatest Common Factor (GCF), '3ab'. 3ab(6 + -5b + -1a) = 0 Ignore the factor 3.Subproblem 1
Set the factor 'ab' equal to zero and attempt to solve: Simplifying ab = 0 Solving ab = 0 Move all terms containing a to the left, all other terms to the right. Simplifying ab = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(6 + -5b + -1a)' equal to zero and attempt to solve: Simplifying 6 + -5b + -1a = 0 Reorder the terms: 6 + -1a + -5b = 0 Solving 6 + -1a + -5b = 0 Move all terms containing a to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -1a + -6 + -5b = 0 + -6 Reorder the terms: 6 + -6 + -1a + -5b = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1a + -5b = 0 + -6 -1a + -5b = 0 + -6 Combine like terms: 0 + -6 = -6 -1a + -5b = -6 Add '5b' to each side of the equation. -1a + -5b + 5b = -6 + 5b Combine like terms: -5b + 5b = 0 -1a + 0 = -6 + 5b -1a = -6 + 5b Divide each side by '-1'. a = 6 + -5b Simplifying a = 6 + -5bSolution
a = {6 + -5b}
| 2(4y-9)=5(y-4) | | 2x^4-3x^3+5x^2+5x-7=0 | | 1/(x+9)^2 | | 32/4(8) | | .10x+.25y=7.45 | | 2x+6=7x-2 | | 2(5x+4)=2(3m-10) | | 1/2q-1=6 | | 38-4x=5x+16 | | 7/8x+1/2=7/8 | | 34x+5=10 | | (6x+7/6)+(3/2)=-2x/7 | | -4-2x=12-8x | | x^4-18x^3+81x^2=0 | | 3(x+4)-4(x-3)= | | (6x+7/6)+(3/2)=-2 | | 2q-1=6 | | 4v^2-20v=0 | | 11-8x=139-36x | | 75-4x=14-8x | | x*3a=27 | | ((x-4)+1)/(x+1)=1/2 | | 5x^2+6x-12=2x | | 13b*17= | | 14n-21/7 | | 1/3x+5/6x=7/8 | | 8+(5-4x)-(1-x)=5x-2(x-3) | | 0.7/x=21 | | 7x+12=6+5x | | y=75+20x | | 8(c-2)-(c+3)= | | ((7x-1)/4)-1/3(2x-(1-x)/2)=19/3 |